2023
DOI: 10.1177/00469580231155296
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Psychological Resilience of Emergency Room Nurses Under Public Health Emergencies

Abstract: Resilience is essential for frontline health workers to cope with the unfavorable situations, especially under public health emergencies. Emergency room (ER) nurses are a special cohort of health professionals that may present moderate level of resilience. This study aimed to identify factors that are correlated with resilience in this special cohort to provide directions for intervention and management. ER nurses that have encountered a public health emergency within 3 months were recruited using purposive sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Individual capabilities are seen as the cornerstone of the entire emergency response capability system ( 25 ). Participants reported that professionals should respond to public health emergencies with a conscientious and responsible attitude, good mental and physical fitness, and a spirit of saving lives and helping with injuries ( 26 , 27 ). Medicine is an ever-developing discipline, and professionals need to commit to active learning and regular participation in emergency drills and courses related to emergency management.…”
Section: Resultsmentioning
confidence: 99%
“…Individual capabilities are seen as the cornerstone of the entire emergency response capability system ( 25 ). Participants reported that professionals should respond to public health emergencies with a conscientious and responsible attitude, good mental and physical fitness, and a spirit of saving lives and helping with injuries ( 26 , 27 ). Medicine is an ever-developing discipline, and professionals need to commit to active learning and regular participation in emergency drills and courses related to emergency management.…”
Section: Resultsmentioning
confidence: 99%
“…The procedures used in this study are briefly presented in the flow chart (Figure 1). The questionnaire was designed based on the previously published literature (13,14) and the Emergency Regulations for PUBLIC HEALTH EMERGENCIES (Revised 2022). A small-scale drop-in was conducted after the questionnaire was designed, reaching Cronbach's α of 0.746 and KMO (Kaiser-Meyer-Olkin) of 0.798.…”
Section: Methodsmentioning
confidence: 99%
“…In the pretest, the average score of psychological resilience of emergency nurses was 65.66 ± 1.10, which was at the medium level, consistent with the results of other researchers [ 12 ]. Under a public health emergency, the surge of patients inevitably induced increased workload, prolonged procedures, and fatigue, which all challenged the physical tolerability of emergency department nurses, and subsequently difficulties in adapting with the busy schedule and reduced resilience [ 20 ]. The study which was conducted during the COVID-19 pandemic shows that resilience among emergency nurses is indeed low.…”
Section: Discoursementioning
confidence: 99%